Factors Affecting the Performance of Inpatient Nurses at RSU Bina Kasih Medan in 2023 - Simanjuntak, Monica; Theo, Deli; Nasution, Ramadhani Syafitri (PROMOTOR, 2024)
Nurses are a key factor in improving the quality of services in hospitals because they have a vital role in providing care and support to patients. However, the assessment of nurses' performance showed that the results were not optimal, with achievement only reaching 47%. This can hurt the quality of hospital services. This study aims to identify and analyze factors that influence the performance of inpatient nurses at Bina Kasih Hospital, Medan. The research method used is cross-sectional with a quantitative approach. The sample consisted of 74 inpatient nurses selected using total sampling techniques. Data analysis was carried out through univariate, bivariate, and multivariate analysis using logistic regression tests. The results of the analysis show that workload, work stress, work environment, work intensity, and compensation have a significant effect on the performance of inpatient nurses at Bina Kasih Hospital, Medan (p < 0.05). The implication of this research is the importance of hospital management to pay attention to these factors to improve nurse performance and service quality in hospitals.